Animal welfare for production and working animals: evidence and need for action - Doyle, Rebecca; Cripps, A.; Marry, A.; Wieland, Barbara; Whay, B.; Lindsay, B.; Gallardo, C.M.; Di Leonardo, F.; Huang, H.; Stark, J.; Keeling, L.; Mainar, M.S.; et al. (Food and Agriculture Organization of the United Nations, 2025)
The goal of this technical paper is to draw attention to the importance of animal welfare and how it connects to wider social, environmental, and agricultural issues. It focuses on how animal welfare improvements within farming systems can lead to other benefits, as well as benefiting the animals themselves. The examples throughout this paper demonstrate how sustainable livestock systems can benefit when animal welfare is incorporated as a priority. It is hypothesized that many more opportunities for welfare and sustainability gains exist. To identify these, and to mitigate situations that create trade-offs, system changes need to be grounded by evidence of improvements and include animal welfare assessment.